Utilizing X as a media to improve writing ability on an analytical exposition text for EFL high school students - Lukitaningtyas, Pinurih; Setiyadi, Bambang; Nurweni, Ari (English Language Education Study Program, 2025)
This study focuses on evaluating the writing skills of EFL high school students through analytical exposition after they utilized X. It was carried out with eleventh grade students at SMAS Al-Kautsar Bandar Lampung during the first semester of the 2024/2025 academic year. The sample was class IX.3, which consisted of 36 students. The research used pretest and posttest design. The data were gathered through those tests, which involved writing analytical exposition texts, and were analyzed using a Paired Sample t-test at a significance level of 0.05. The findings indicated a notable enhancement in the students' writing skills after using X as a learning media; the average scores from the pretest and posttest reflected this change. The pretest scores enhanced from 74.06 to 85, showing an improvement of 10.94 points. Additionally, the two-tailed significance value was less than 0.001. Therefore, it can be concluded that teaching analytical exposition texts using X effectively improves the students' writing abilities.